Electronic Spectral Parameters of the Saturated Solutions of Some Amino Acids and Some Bioactive N-Heterocyclic Compounds Doped with Pr(III) Ion - Verma, R.S.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
Electronic spectral parameters, viz., Judd-Ofelt parameter (Tλ), Racah (Ek), Slater-Condon (Fk), Lande (ζ4f) and bonding parameters ( β ,b1/2 and δ ) have been evaluated for the saturated solutions of some amino acids (L-cystine, L-Ieucine, L-proline, L-threonine, arginine, β-alanine and DL-aspartic acid) and some bio-active N-heterocyclics (indole, 4-aminoantipyrine, 1,2,3-benzotriazole and uracil) doped with Pr(III) ion. The change in symmetry around Pr(III) ion and covalency in M-L interactions is observed. A linear relationship between oscillator strength (Ped) and vT6 has beeen observed for hypersensitive transition (3H4 →3P2).